Why Complementarity Matters for Stability-Hong Kong SAR and Singapore as Asian Financial Centers - Le Lesle, Vanessa (IMF Working Papers; Working Paper ;, 2014)
There is much speculation regarding a 'race for dominance' among financial centers in Asia, arising from the anticipated financial opening up of China. This frame of reference is, to an extent, a predilection that results from a traditional understanding of financial centers as possessing historical, geographic, and scale economy advantages. This paper, however, suggests that there is an alternative prism through which the evolution of financial centers in Asia needs to be viewed. It underscores the importance of 'complementarity' rather than 'dominance' to better serve regional and global financial stability. We posit that such complementarity is vital, through network analysis of the roles of Hong Kong SAR and Singapore as the current leading financial centers in the region. This analysis suggests that a competition for dominance can result in de-stabilizing levels of interconnectivity that render the global 'network' as a whole more susceptible to rapid propagation of shocks. We then examine the regulatory and policy challenges that may be encountered in furthering such complementary coexistence.